Performance evaluation of an FDDI - ATM gateway by simulation method / Wan Aini Ahmad - Ahmad, Wan Aini (1995)
Local Area Network (LANs) have been designed for communication covering small sites. Besides, a Fiber Distributed Data Interface (FDDI) provides very high speed interconnection to several other LANs using fibre optics as a physical medium. The existence of Asynchronous Transfer Mode (ATM), which is the most promising transmission techniques for Broadband ISDN (B-ISDN) caters for a variety of users services. Examples of these services are video telephony, video conferencing, electronic mail, voice mail and broadcast television. The aim of this project is to investigate the performance of interconnection between FDDI Metropolitan Area Network (MAN) and ATM-based B-ISDN, through a gateway unit. This project uses a simulation model to evaluate the performance of the FDD1-ATM gateway. The simulation code is written in C and uses a timed token service discipline, which include Token Rotation Time (TRT) and Token Holding Time (TUT). The effect of load passing through the FDDI-ATM gateway is investigated, and the performance of interest, Mean Waiting Time (MWT) is noted.